Eliciting primes from narratives of integrity - Largoza, Gerardo L. (Animo Repository, 2022)
In this work, we bring several social science approaches to bear on the study of integrity: Malabed and Joaquin use discourse analysis and cognitive mapping to describe how integrity is conceptualised in two Republic Acts (3019 and 6713) as well as in popular discourse. Malabed finds that, as a concept, integrity (dangal) has evolved, initially drawing meaning almost exclusively from legal and moral discourses in R.A. 3019 to broader, more varied discourses such as patriotism, simplicity, and loyalty in the more recent R.A. 6713. Joaquin finds, however, that despite the appeal of R.A. 6713 primarily to contemporary secular values, gaps are seen when one examines how the general public, sampled from discussions of high-profile corruption cases in blog commentaries and radio transcripts, forms its notions and parameters of integrity. These gaps ought to be taken more seriously if the law is to function not simply as a statement of ideals but as a real, internalised, guide to action. Finally, Largoza employs behavioural economics in the search for "primes" for ethical behaviour: i.e., subtle environmental cues that can lead people to desirable behaviour, often without recourse to (expensive) incentives or the (stress-inducing) threat of force. They do this by exploiting deeply-rooted ("hard-wired") cognitive biases, using them as a basis upon which to design behaviourally-sensitive rules, policies, etc. To provide preliminary evidence of the efficacy of these primes, he initially ran seven experiments, designed and implemented in collaboration with DLSU Economics undergraduates over the period September to December 2010. Given the limited research budget, the experiments are small-scale and are best treated! as "pilots", and only the four that yielded promising results are featured here. However, the designs and instructions are available for replication and have yielded interesting preliminary results. Among them are the following: that individuals respond to the variety in rewards for ethical e than the value of rewards; that priming empathy can create a flexible yet optimal norm; that people tend to be more forgiving toward the unethical acts of people of status, even when the source of status is totally artificial; and that the temptation to engage in unethical behaviour is more likely to be restricted by the availability of internal attributions rather than external ones.